High-impact details of play and movements in female basketball game - Nagano, Y.; Sasaki, S.; Shimada, Y.; Koyama, T.; Ichikawa, H. (Sports Medicine International Open, 2021)
This study aimed to identify the high-impact details of play and movements with higher acceleration and their frequency during a female basketball match. Trunk acceleration was measured during a simulated basketball game with eight female players. The extracted instance was categorized, which generated at > 6 and 8 G resultant accelerations using a video recording and an accelerometer attached to the players` trunk, as details of play and movements. The frequency and ratio of the details of play and movements regarding all detected movements were calculated. A total of 1062 and 223 play actions were detected for the resultant acceleration thresholds of > 6 and 8 G, respectively. For these acceleration thresholds, in terms of details of play, positioning on the half-court was the most frequently observed (29.6 and 23.8%, respectively). In terms of movements, deceleration was the most frequently detected movement (21.5 and 23.3%, respectively), followed by landing (7.6 and 15.7%, respectively). Deceleration during positioning on the half-court and defense as well as landing mostly after a shot were detected as high-impact frequent basketball-specific movements. The results also showed that characteristics of movements or playing style and playing position may have an effect on acceleration patterns during a basketball game.